1991
DOI: 10.1002/mmce.4570010105
|View full text |Cite
|
Sign up to set email alerts
|

The effects of electromagnetic coupling on MMIC design

Abstract: The undesired effects of electromagnetic coupling between passive elements in MIC and MMIC designs are examined. Measured data of several strongly coupled circuit topologies commonly encountered in MMIC design are compared to simulations using circuit theory programs employing discontinuity models as well as electromagnetic field simulation tools. The results of this comparison are used to derive a set of specifications for a simulation tool suitable for use in the design of MIC and MMIC circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Except for a slight frequency shift which can be attributed to the variability in the slab permittivity, the simulated 18121 agrees well with the measured values. For this particular structure, most transmission-line based circuit simulators did not predict the double resonance observed near 10 GHz because the phenomenon was caused by unexpected parasitic couplings between the two tees [5].…”
Section: Post-processingmentioning
confidence: 97%
“…Except for a slight frequency shift which can be attributed to the variability in the slab permittivity, the simulated 18121 agrees well with the measured values. For this particular structure, most transmission-line based circuit simulators did not predict the double resonance observed near 10 GHz because the phenomenon was caused by unexpected parasitic couplings between the two tees [5].…”
Section: Post-processingmentioning
confidence: 97%
“…Equations (2) and (3) For large spacing (s/w » 1), the coupling capacitance C^2^^< 3 inductance L^2 become small. In this case, the propagation constants in eq ( 2 ) approach that of an isolated line 7^:…”
Section: Coupled Line Equationsmentioning
confidence: 99%
“…In dense circuits, electromagnetic coupling (crosstalk) between closely spaced signal lines limits interconnect performance [1] and becomes an important aspect of circuit design [2]. The organization of this report is as follows.…”
Section: Introductionmentioning
confidence: 99%
“…This double-Tee structure is particularly interesting because the double-resonance phenomenon observed in the ISI21 plot was unexpected. Laboratory experiments have shown that this phenomenon was caused by mutual coupling between the two Tees [20]. Since most existing CAD circuit simulators are lumped-element based, they failed to predict this occurrence because they cannot take this type of secondary effect into account.…”
Section: Examplesmentioning
confidence: 99%